Вплив агрегації бензоіндосквараїнів на генерацію синглетного кисню - Синюгіна, А.Т.; Іщенко, О.О. (Доповіді НАН України, 2023)
Методом електронної абсорбційної і флуоресцентної спектроскопії з використанням пасток показано, що бензоіндосквараїн з гідрофобним бічним радикалом сенсибілізує утворення синглетного кисню ефективніше, ніж його аналог з гідрофільним радикалом, зі зростанням відсотка води в ДМСО і етанолі. Встановлено, що це обумовлено більшою схильністю до агрегації першого порівняно з другим. Показано, що агрегат має сендвічеву будову, що сприяє активації сенсибілізації синглетного кисню за рахунок триплет-триплетного переносу енергії. The effect of aggregation of benzoindosquaraines on singlet oxygen generation was investigated using electronic absorption and fluorescence spectroscopy in the presence of traps. The results demonstrate that benzoindosquarine with a hydrophobic side radical sensitizes the formation of singlet oxygen more effectively compared to its analog with a hydrophilic radical, especially as the percentage of water in DMSO and ethanol increases. This difference in sensitization efficiency is attributed to the higher propensity of the former to aggregate, in contrast to the latter. The study further reveals that the aggregate adopts a sandwich structure, which facilitates the activation of singlet oxygen sensitization through triplet-triplet energy transfer.